Dentoalveolar Defects in the Hyp Mouse Model of X-linked Hypophosphatemia. (April 2020) - Zhang, H.; Chavez, M.B.; Kolli, T.N.; Tan, M.H.; Fong, H.; Chu, E.Y.; Li, Y.; Ren, X.; Watanabe, K.; Kim, D.G.; Foster, B.L.
Mutations in PHEX cause X-linked hypophosphatemia (XLH), a form of hypophosphatemic rickets. Hyp ( Phex mutant) mice recapitulate the XLH phenotype. Dental disorders are prevalent in individuals with XLH; however, underlying dentoalveolar defects remain incompletely understood. We analyzed Hyp mouse dentoalveolar defects at 42 and 90 d postnatal to comparatively define effects of XLH on dental formation and function. Phex mRNA was expressed by odontoblasts (dentin), osteocytes (bone), and cementocytes (cellular cementum) in wild-type (WT) mice. Enamel density was unaffected, though enamel volume was significantly reduced in Hyp mice. Dentin defects in Hyp molars were indicated histologically by wide predentin, thin dentin, and extensive interglobular dentin, confirming micro–computed tomography (micro-CT) findings of reduced dentin volume and density. Acellular cementum was thin and showed periodontal ligament detachment. Mechanical testing indicated dramatically altered periodontal mechanical properties in Hyp versus WT mice. Hyp mandibles demonstrated expanded alveolar bone with accumulation of osteoid, and micro-CT confirmed decreased bone volume fraction and alveolar bone density. Cellular cementum area was significantly increased in Hyp versus WT molars owing to accumulation of hypomineralized cementoid. Histology, scanning electron microscopy, and nanoindentation revealed hypomineralized "halos" surrounding Hyp cementocyte and osteocyte lacunae. Three-dimensional micro-CT analyses confirmed larger cementocyte/osteocyte lacunae and significantly reduced perilacunar mineral density. While long bone and alveolar bone osteocytes in Hyp mice overexpressed fibroblast growth factor 23 ( Fgf23 ), its expression in molars was much lower, with cementocyte Fgf23 expression particularly low. Expression and distribution of other selected markers were disturbed in Hyp versus WT long bone, alveolar bone, and cementum, including osteocyte/cementocyte marker dentin matrix protein 1 ( Dmp1 ). This study reports for the first time a quantitative analysis of the Hyp mouse dentoalveolar phenotype, including all mineralized tissues. Novel insights into cellular cementum provide evidence for a role for cementocytes in perilacunar mineralization and cementum biology.